2018 Vegetable Production Guide Chapter 6: Cole Crop Production - Lincoln Zotarelli; Peter J. Dittmar; Monica Ozores-Hampton; Nicholas S. Dufault; Bonnie Wells; Johan Desaeger; Joseph W. Noling; Eugene J. McAvoy; Qingren Wang; Christian F. Miller (EDIS, 2018)
This 21-page fact sheet is chapter 6 of the 2018 Vegetable Production Handbook. Written by Lincoln Zotarelli, Peter J. Dittmar, Monica Ozores-Hampton, Nicholas S. Dufault, Bonnie Wells, Johan Desaeger, Joseph W. Noling, Eugene J. McAvoy, Qingren Wang, and Christian F. Miller, and published by the Horticultural Sciences Department, 2018.